(untitled) - Gerardi, Kellie; Wilson, Allyson ([Coral Gables, Florida], 2023)
"Luna Munas science class is hosting a bake sale fundraiser, but running a bakery isnt as easy as it looks! Just when everything is starting to look like one giant, galactic mess, Luna Muna discovers that teamwork and creativity just might be able to save the day... and the treats!"--Provided by publisher.
Keywords: Fiction; Fiction; Bakers and bakeries; Fiction; Baking; Imagination; Fiction; Astronauts; Fiction; Girls; Juvenile fiction; Bakeries; Outer space; Fiction; Picture books; Picture books